UJI EKSPERIMENTAL KINERJA E-CAR EASY PARKING PENGGERAK 2 MOTOR BLDC 350 WATT - Bambang Setyono; Ayu Setyaning Sayekti Poesoko; Reka Fariz Nugroho (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
People need electrical energy for both household and daily vehicles, for example, electric cars (e-cars). In this study, an electric car also has the innovation of easy parallel parking (easy parking). The easy- park e-car operates the same as a car in general, but the difference is in the working system. Two BLDC 36 volts 350 watts motor main drivers, one 36 volts 350 watts controller, and one 12 volts 12 ah SMT battery were used. The Easy Park e-car (easy park electric car) can be operated with a maximum of 2 passengers, having a maximum weight of 150 kg and a top speed of 27 km/hour. While using 1 passenger, the top speed was 30 km/hour. A driver could have a minimum turning radius of the vehicle of 2.25 meters. To test the easy parking, e-car innovation was carried out by turning the rear wheel arm angle electrically and turning the front angle manually until the wheels rotated at 90°, intended to determine the performance of the electric car when doing parallel parking. After analyzing the minimum turning radius, it can be concluded that the smaller the minimum turning radius, the easier the vehicle will pass. Meanwhile, the top speed of the vehicle of 30 km/h occurred at a distance of 2 kilometres and an average speed of 10–20 km/h using the geo tracker app.